2009
DOI: 10.1111/j.1365-2486.2009.01978.x
|View full text |Cite
|
Sign up to set email alerts
|

Elevated atmospheric carbon dioxide and ozone alter soybean diseases at SoyFACE

Abstract: Human driven changes in the Earth's atmospheric composition are likely to alter plant disease in the future. We evaluated the effects of elevated carbon dioxide (CO 2 ) and ozone (O 3 ) on three economically important soybean diseases (downy mildew, Septoria brown spot and sudden death syndrome-SDS) under natural field conditions at the soybean free air concentration enrichment (SoyFACE) facility. Disease incidence and/or severity were quantified from 2005 to 2007 using visual surveys and digital image analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
93
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(101 citation statements)
references
References 34 publications
(69 reference statements)
3
93
0
Order By: Relevance
“…This can lead to increased levels of foliar diseases that are favored by moist conditions. For example, brown spot, caused by Septoria glycines, can start moving up the canopy earlier on soybeans planted in narrow rows [38]. High plant populations can also make soybeans more susceptible to diseases such as charcoal rot and Sclerotinia stem rot.…”
Section: Planting Dates and Densitiesmentioning
confidence: 99%
“…This can lead to increased levels of foliar diseases that are favored by moist conditions. For example, brown spot, caused by Septoria glycines, can start moving up the canopy earlier on soybeans planted in narrow rows [38]. High plant populations can also make soybeans more susceptible to diseases such as charcoal rot and Sclerotinia stem rot.…”
Section: Planting Dates and Densitiesmentioning
confidence: 99%
“…Several studies in open-top field chambers indicated that soybean yield has already been under threat at current O 3 concentrations [3,8], with dramatic yield loss of 53% by ambient air in Pakistan [9]. An increase of O 3 concentration from 30 to 60 ppb for 7 h day −1 could decrease soybean yield by 16% [10], and greater yield loss under higher O 3 concentration [11].…”
Section: Introductionmentioning
confidence: 99%
“…Phytophthora citricola on Fagus sylvatica seedlings under elevated CO 2 and N fertilization; Fleischmann et al 2010). Free-Air CO 2 Enrichment (FACE) facilities can deliver useful insights on how plant pathosystems are likely to be affected by the interactions among global change factors (Eastburn et al 2009(Eastburn et al , 2011. There is a need to include in such studies various plant disease management approaches, including The pathogen was introduced into Switzerland from SouthWest Germany in the 1980s (this explains why the climatically more suitable Ticino has been less affected by fire blight than northern Swiss Cantons).…”
Section: Interactions Among Global Change Factorsmentioning
confidence: 99%